Micromechanical finite element simulations of crack propagation in silicon nitride - Wippler, Johannes (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2012)
Silicon nitride is used for challening applications like cutting inserts or forming rolls. The extreme strength and toughness of the material is achieved by an interaction between the microstructure and fracture behaviour on the microlevel. In order to understand these mechanisms, detailed unit cells have been defined and used for the determination of the effective fracture properties. The results have been used for the implementation of an effective continuum damage mechanics model.